DEVELOPMENT OF AN OBSERVATIONAL TOOL TO ASSESS QUALITY OF EXERCISE PERFORMANCE BY PARTICIPANTS IN A NEUROMUSCULAR INJURY PREVENTION PROGRAM. Issue 7 (11th March 2014) - Fortington, L; Finch, CF; Donaldson, A; Lathlean, T; Cook, J; Gabbe, B; Lloyd, D; Young, W
Abstract : Background: In determining the effectiveness of sports injury prevention programs (IPP), an assessment of program fidelity is needed. This includes considering whether the intervention was delivered and adhered to as it was intended. Evaluation of program fidelity prevents incorrect conclusions being made about the effects of an IPP and can provide information on why it was successful, or not. Program fidelity for IPPs in sport has generally been limited to self-reported measures around frequency of participation. However, for exercise-based IPPs, performing the exercises as they were originally prescribed is important to maximise injury prevention benefits. Therefore, observing the actual exercise performance could give important insight when evaluating overall IPP fidelity. Objective: The aim of this study was to develop an observational tool for exercise-based IPPs and assess its inter-rater reliability. This was trialled in the context of FootyFirst, an IPP in Australian Football. Design: The essential performance criteria of each FootyFirst exercise were described in terms of their technique, volume and intensity, in line with exercise prescription guidelines. The expert FootyFirst development team were consulted until consensus was reached on details of each exercise. Each criterion was evaluated by observing player performance and responding with a yes/no answer. Setting: Community Australian football clubs. Participants: Players participating in FootyFirst as part of regular training; two independent raters. Main outcome measurements: Inter-rater reliability of tool and correct performance of FootyFirst exercises. Results: The observational tool was trialled at eight clubs for 70 observations. The raters agreed on 61 observations (K=0.718, P<.001; substantial agreement), of which 41(67%) scored yes for all performance criteria (technique, volume and intensity), indicating the exercise was performed as prescribed. Conclusions: The FootyFirst Observational Tool has high inter-rater reliability. This can be used to monitor the quality of exercise performance when assessing overall program fidelity.